A Secret Image Sharing Method Using Integer Wavelet Transform. (28th August 2007) - Huang Huang, Chin-Pan Chin-Pan; Li Li, Ching-Chung Ching-Chung
Abstract : A new image sharing method, based on the reversible integer-to-integer (ITI) wavelet transform and Shamir's( r, m ) threshold scheme is presented, that provides highly compact shadows for real-time progressive transmission. This method, working in the wavelet domain, processes the transform coefficients in each subband, divides each of the resulting combination coefficients intom shadows, and allows recovery of the complete secret image by using anyr or more shadows( r ≤ m ) . We take advantages of properties of the wavelet transform multiresolution representation, such as coefficient magnitude decay and excellent energy compaction, to design combination procedures for the transform coefficients and processing sequences in wavelet subbands such that small shadows for real-time progressive transmission are obtained. Experimental results demonstrate that the proposed method yields small shadow images and has the capabilities of real-time progressive transmission and perfect reconstruction of secret images.